Stachydrine ameliorates high‐glucose induced endothelial cell senescence and SIRT1 downregulation. Issue 11 (13th September 2013) - Servillo, Luigi; D'Onofrio, Nunzia; Longobardi, Lara; Sirangelo, Ivana; Giovane, Alfonso; Cautela, Domenico; Castaldo, Domenico; Giordano, Antonio; Balestrieri, Maria Luisa
ABSTRACT Hyperglycaemia, a characteristic feature of diabetes mellitus, induces endothelial dysfunction and vascular complications by accelerating endothelial cell (EC) senescence and limiting the proliferative potential of these cells. Here we aimed to investigate the effect of stachydrine, a proline betaine present in considerable quantities in juices from fruits of the Citrus genus, on EC under high‐glucose stimulation, and its underlying mechanism. The senescence model of EC was set up by treating cells with high‐glucose (30 mM) for different times. Dose‐dependent (0.001–1 mM) evaluation of cell viability revealed that stachydrine does not affect cell proliferation with a similar trend up to 72 h. Noticeable, stachydrine (0.1 mM) significantly attenuated the high‐glucose induced EC growth arrest and senescence. Indeed, co‐treatment with high‐glucose and stachydrine for 48 h kept the percentage of EC in the G0/G1 cell cycle phase near to control values and significantly reduced cell senescence. Western blot analysis and confocal‐laser scanning microscopy revealed that stachydrine also blocked the high‐glucose induced upregulation of p16INK4A and downregulation of SIRT1 expression and enzyme activity. Taken together, results here presented are the first evidence that stachydrine, a naturally occurring compound abundant in citrus fruit juices, inhibits the deleterious effect of high‐glucose on EC and acts through the modulation of SIRT1 pathway. These results may open new prospective in the identification of stachydrine as an important component of healthier eating patterns in prevention of cardiovascular diseases. J. Cell. Biochem. 114: 2522–2530, 2013. © 2013 Wiley Periodicals, Inc.